PENGEMBANGAN USAHA NUGET MENGGUNAKAN LIMBAH UDANG DI KECAMATAN MEDAN LABUHAN KOTA MEDAN - Yuspa Hanum; Tukiman Tukiman; Salim Salim (Universitas Negeri Medan, 2015)
Shrimphas anti-inflammatoryandhelpreducegumswelling. Shrimp isvitaminD, regulates theabsorption ofcalciumandphosphorusareservesforstrongbones andteeth. Shrimp is agood source ofvitaminB12, is important forproper brain functionandessentialforthe formationandmaturationof redbloodcells.Prawnsarealsoagoodsourceofomega-3fattyacids,reducestheriskofcardiovascularproblemsbecauseitreducescholesterolintheblood.Prawnsalsohavelean proteinandlow in calories. Untilnow, theshrimpprocessingerrorsstilloccur,becausein generalpublicuseshrimpas foodis only68% oftheshrimp(just meat), while only32%oftheshrimpinthe exhaustaswastesuch asthe head, skinandtailshrimp. While thenutrient contentinshrimpis notonlythe meatalonebutincludinghead, skinandtailshrimp,indeedinfactthe head, skinandtailshrimpconsumedbut canbe difficulttodilakukakanotheralternativesintheprocesssuch asrawmaterialis processed intonuggets, sausagesandmeatballsspicesandraw materialsasanadditive infoodssuch asboilednoodles, friednoodles, fried riceandotherfoods. So thatthe nutrientsarenotwastedon theshrimp-itaswaste. lack ofhuman resourcesandbusiness groupsnuggetsnuggetslength oftheproductionprocessbecameone of themajor factorsin thenuggetsseizebusinessopportunitiesandexpectationsof thebusiness groupfor a solutioninstages(1) knowledge ofhow to createagoodandtruenuggetsas well asnutritious, (2) processlarge-scale manufacture ofnuggets, (3) agoodpackaging designnuggets. alternativesolutionsin order to increaseknowledge(SDM) nuggetsofmakinggoodandright, capacityand quality productionnuggets